2019
DOI: 10.1089/cyber.2019.0341
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Effects of Exergames for Children and Adolescents with Obesity: A Systematic Review and Meta-Analysis

Abstract: The systematic review and meta-analysis were conducted to analyze the psychological effects of exergames for children and adolescents with overweight or obesity. In August 2018, the electronic databases searched were PubMed, Scopus, Web of Science, SPORTDiscus, Science Direct, CINAHL, and PsycINFO. The eligibility criteria were defined according to the population, intervention, comparison, outcome, and study design. In relation to the population, only studies with children or adolescents with overweight or obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 55 publications
1
29
0
4
Order By: Relevance
“…Seventeen studies were included [18,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], from which 7 were systematic reviews and meta-analysis [18,32,33,36,37,44,45]. All studies focused on children and adolescents of both sexes with an age ranged from 3 to 19 years.…”
Section: Characteristics Of Systematic Reviews or Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen studies were included [18,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], from which 7 were systematic reviews and meta-analysis [18,32,33,36,37,44,45]. All studies focused on children and adolescents of both sexes with an age ranged from 3 to 19 years.…”
Section: Characteristics Of Systematic Reviews or Meta-analysismentioning
confidence: 99%
“…Ten systematic reviews presented data on physical fitness, here defined as maximal oxygen uptake, heart rate, energy intake, and increased physical activity of children/adolescents [18,30,31,34,36,38,[41][42][43][44]. Seven reviews of predominantly low to moderate quality showed the effects of AVGs on some aspects of physical functioning [18,30,36,38,[41][42][43].…”
Section: Effects On Physical Fitnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially in children, the impact of early inclusion into digital electronic activities has sparked interest in research on learning, sleep, and the relationship between these electronic activities and their effect on well-being and mental health [6][7][8][9]. Despite the negative effects, it has recently become possible to observe the potential benefits that technology can have on mental health and the involvement of physical activity [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%